Pemahaman Umat Awam Tentang Buah Sakramen Pengurapan Orang Sakit di Stasi Maria Ratu Damai Kolongan, Paroki Santo Yohanes Penginjil Laikit - Paulus Titus Maru (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
This study examines the understanding of Catholic laypeople regarding the fruits of the Sacrament of the Anointing of the Sick at Stasi Maria Ratu Damai Kolongan. The research was conducted to identify the level of understanding among the faithful and to determine aspects that still require further catechetical formation. A quantitative descriptive method was employed using questionnaires distributed to 47 respondents. The findings indicate that, in general, the respondents possess a good understanding of the fundamental meaning and spiritual fruits of the sacrament. Most participants recognize the sacrament as a source of spiritual strength, consolation, courage, union with the suffering of Christ, forgiveness of sins, and preparation for eternal life. However, the study also reveals several misconceptions among the faithful, particularly regarding the possibility of physical healing through the sacrament, its relationship with the forgiveness of sins, and the perception that it is intended only for those approaching death. These findings suggest the need for more systematic and contextual catechesis to deepen the faithful’s understanding of the sacrament. Through proper catechetical formation, the faithful can better appreciate the Sacrament of the Anointing of the Sick as a sign of Christ’s healing presence and saving grace in times of suffering and illness.